Calculating the impact of COVID-19 pandemic on child abuse and neglect in the U.S. (August 2021) - Nguyen, Loc H.
Abstract: Background: COVID-19 has had a major impact on child abuse and neglect (CAN) in the U.S. leading to a change in the number of reported screened-in CAN investigations, missed prevention cases, and missed CAN cases. Objectives: To estimate the deficit number of CAN investigations and resultant estimated number of missed prevention and CAN cases due to the COVID-19 pandemic in the U.S. from March 2020 to December 2020. Methods: Secondary data analyses of administrative child welfare data from January 2013 to December 2020 from New York City, Florida, New Jersey and Wisconsin were conducted. Spline regression modeling controlling for autocorrelation was utilized to explore any significant changes once the pandemic began in March 2020 in the number of screened-in CAN investigations. The seven-year monthly average of screen-in CAN investigations for March through December from 2013 to 2019 was calculated and compared to the numbers of CAN investigations for March 2020 to December 2020. The resultant number of missed prevention cases and CAN cases was estimated for the four jurisdictions and used to approximate the number of missed prevention cases and CAN cases in the U.S., as well as the projected estimation of national lifetime economic costs. Results: Prior to the pandemic, there were insignificant monthly increases of 0.7 CAN investigations in NYC and 6.2 CAN investigations in Florida, a significant monthly increase 4.2 CAN investigations in New Jersey and an insignificant monthly decrease in 0.6 CAN investigations in Wisconsin. Once the pandemic began, there were significant monthly decreases (p < .001) in each of the four jurisdictions, including 1425.6 fewer CAN investigations in NYC, 3548.0 fewer CAN investigations in Florida, 963.0 fewer CAN investigations in New Jersey and 529.1 fewer CAN investigations in Wisconsin. There were an estimated 60, 791 fewer CAN investigations in these four jurisdictions from March 2020 to December 2020 of which there were approximately 18, 540 missed prevention and CAN cases suggesting up to 4.2 billion in lifetime economic costs. It was estimated that were 623, 137 children not investigated for CAN in the U.S. during the same 10-month period. This suggests that there were an estimated 85, 993 children were missed for prevention services and about 104, 040 children were missed for CAN with a potential lifetime economic impact of up to 48.1 billion in the U.S. Conclusions: The COVID-19 pandemic has led to a precipitous drop in CAN investigations where almost 200, 000 children are estimated to have been missed for prevention services and CAN in a 10-month period. There are opportunities for the child welfare jurisdictions to work with partner education, public health, social service and other providers to strategically approach this very grave issue in order to mitigate its impact on this very vulnerable population.